Helen and Newton Harrison Academic Media Services, University of Colorado, Boulder ; producer, James Johnson. - Harrison, Helen Mayer, 1927-2018; Harrison, Newton, 1932-2022; Johnson, James (James Alan); Crane, Michael, 1948- (What follows--, 1988)
Helen and Newton Harrison are ecological artists whose approach to making art involves finding solutions to ecological problems. The husband and wife team both teach at the University of California, San Diego.